Analisis Peluang dan Tantangan Perdagangan Produk Pertanian Subsektor Hortikultura (Studi Kasus Impor Indonesia-Tiongkok) - Annisa Nurul Shanty (CV. ITTC INDONESIA, 2026)
Trade in horticultural products between Indonesia and China continues to evolve in tandem with rising domestic demand and global economic integration. This study aims to analyze the opportunities and challenges faced by Indonesia in horticultural trade, particularly in the context of imports from China. The method used is a qualitative descriptive approach with secondary data sourced from publications by the Central Statistics Agency (BPS), the Ministry of Agriculture, and relevant scientific literature. The results indicate that the value of Indonesia’s horticultural imports from China continues to rise, with China accounting for approximately 43.41% of the total import value in January 2025. This situation reflects Indonesia’s high dependence on horticultural supplies from China due to the suboptimal state of domestic production capacity. On the other hand, China is also a potential market for Indonesia’s tropical horticultural products, which possess a comparative advantage. However, these opportunities face several challenges, including strict food quality and safety standards, competition with other ASEAN countries, and limitations in logistics infrastructure and agricultural technology. This study concludes that enhancing the competitiveness of Indonesia’s horticultural exports requires an integrated strategy encompassing the adoption of international standards, strengthening the cold chain, diversifying value-added products, and bolstering bilateral cooperation within the ACFTA framework.